Church Hymnography and Music in the Works of the Three Holy Hierarchs - Ignatov, Liubomir (Forum Theologicum Sardicense, 2025)
Liubomir Ignatov, Church Hymnography and Music in the Works of the Three Holy Hierarchs. The article addresses a topic that has not yet been thoroughly explored in theological literature or given its due importance among significant theological subjects. It attempts to briefly present the contributions to church music and hymnography made by three of the most renowned Church Fathers and teachers of the Orthodox Church: Saints Basil the Great, Gregory the Theologian, and John Chrysostom. Utilizing information from their works and biographical writings about them, the article demonstrates their role in the development and establishment of church music and hymnog-raphy during their respective eras. It also highlights the extensive musical and thematic information in their writings, illustrating the relevance and quality of church music in worship, both in their time and prior. Additionally, the article summarizes their valuable guidance on the advancement of church singing and their teachings on the purity and soul-saving mission of Christian poetry and music. It is noted that many of their profound statements have influenced later hymnographers, which is an interesting aspect of Orthodox hymnography highlighted in the present text.